2018
DOI: 10.3390/su10020461
|View full text |Cite
|
Sign up to set email alerts
|

False Barriers in the Purchase of Organic Foods. The Case of Extra Virgin Olive Oil in Spain

Abstract: Although Spain is the world's top organic extra virgin olive oil (OEVOO) producer, domestic consumption is low. Most of the OEVOO produced is destined for external markets. As access to these markets is rife with challenges, developing internal demand has become a matter of utmost importance. Therefore, the general objective of this study is to analyse what is limiting OEVOO consumption levels in Spain. Although a review of the literature reveals some potential explanatory factors, this study analyses the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Another method for increasing demand might consist of adopting sophisticated and targeted marketing strategies [76]. Torres-Ruiz et al [77] consider that one possible strategy could rely on achieving greater social and environmental awareness, in order to encourage organic consumption, or simply link the consumption of the product to important benefits for the consumer (health, quality) [78].…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Another method for increasing demand might consist of adopting sophisticated and targeted marketing strategies [76]. Torres-Ruiz et al [77] consider that one possible strategy could rely on achieving greater social and environmental awareness, in order to encourage organic consumption, or simply link the consumption of the product to important benefits for the consumer (health, quality) [78].…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Spain has become the world's leading producer of both olive oil in general, and extra-virgin olive oil. It is currently recognized, both for the extension of its crops and for the high quality of the product (Torres-Ruiz et al., 2018). The region of Extremadura, located in the southwest of Spain, accommodates, in its two provinces, 135 mills producing olive oil (85 in the province of Badajoz and 50 in the province of Cáceres).…”
Section: Introductionmentioning
confidence: 99%
“…Research Ham et al (2016) proves there are some barriers for consumers to buy organic products that are negative attitude, cost, time, and knowledge. Buder et al (2014) found that the reason consumers do not buy organic products is the price, availability, and quality of the product, in contrast to the results of research Ruiz et al (2018) found that the main barrier consumers do not consume organic products because Spanish consumers have no appreciation against organic labels and tend to disrespect organic products.…”
Section: Introductionmentioning
confidence: 80%
“…Eco-oriented behavior is also shaped by the value that consumers believe is the natural human value orientation (Wijaya, 2017). The results of previous research findings vary widely depending on the conditions of different countries, both on the motives and barriers of consumption of organic products (Ruiz et al, 2018).…”
Section: Introductionmentioning
confidence: 97%